Correlation of mastering effective sentences and learning motivation to writing skills of explanation text for high school students - Yulia Pebriani; Refa Lina Tiawati (BAHASTRA, 2021)
This article aims to describe and describe the relationship between effective sentence mastery and student motivation to write explanatory text skills. The results of data processing using multiple regression to the explanatory text writing variable (Y) resulted in a multiple regression coefficient (b) of 0.094 for effective sentence mastery (X1) and 0.791 for learning motivation (X2) and a constant (a) of 50.547. Thus, the form of the correlation between the three variables can be expressed by the multiple regression equation áºŽ = 50.547 + 0.094X1 + 0.791 X2. The results of the data obtained in the form of a correlation that has a significant value between effective sentence mastery and learning motivation on explanatory text writing skills at the coefficient of determination R2 = 0.375, effective sentence mastery and learning motivation affect explanatory text writing skills by 37.5%.Â